PERANCANGAN IKON CAGAR BUDAYA DAN MANUSKRIP DALAM LOGO OBJEK PEMAJUAN KEBUDAYAAN KOTA BANDUNG - Ramdan, Muhamad Rafli; Nagara, Martien Roos; Hadianto, Hadianto (ATRAT: Jurnal Seni Rupa, 2024)
Icons are one of the main elements in communicating and introducing visual identity to the outside world. The design of cultural heritage icons and manuscripts in the Bandung City Cultural Advancement Object logo is one of the programs created by the Bandung City Government which is also written in Bandung City Regional Regulation No. 7 of 2023 concerning the Advancement of Culture. The Bandung City Disbudpar collaborated with lecturers and students at the Bandung College of Technology majoring in Visual Communication Design in the process of forming a visual identity in the form of the Bandung City OPK logo and icon. The design of cultural heritage icons and manuscripts was created to create a visual identity to preserve the rich history and cultural heritage of the city of Bandung. This icon is designed to include elements typical of cultural heritage and manuscripts. The Cultural Heritage icon represented by the classic architectural form of the roof of Bank Mandiri (EX–nedhandel N.V) on Jalan Asia Afrika No. 01, while manuscript icons can be found in manuscripts, fibers, books and chronicles. It is hoped that the design of the Bandung City OPK icon can become an icon that arouses a sense of pride, increases public awareness of cultural riches, and has an interest in cultural development that attracts the outside world and strengthens the image of the City of Bandung.